2015
DOI: 10.1038/gt.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery to rat and human Schwann cells and nerve segments: a comparison of AAV 1–9 and lentiviral vectors

Abstract: Schwann cells (SCs) in an injured peripheral nerve form pathways for regenerating axons. Although these cells initially support regeneration, SCs lose their pro-regenerative properties following a prolonged period of denervation. Gene transfer to SC can enhance their therapeutic potential. In this article, we compared adeno-associated viral (AAV) vectors based on serotypes 1-9 for their capability to transduce cultured primary rat and human SCs and nerve segments. AAV1 is the best serotype to transduce rat SCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 81 publications
4
21
0
Order By: Relevance
“…In 2015, Tanguy et al [60] observed a cell transduction in the sciatic nerve of mice intravenously injected with AAV2/9 one day after birth but no detail on the cell type was provided. Hoyng et al described in 2015 the transduction efficiency of AAV2/1 to 9 in rat and human Schwann cells in vitro and in sectioned mouse nerve segments undergoing demyelination ex vivo [26]. As the existing data was inconclusive, we tested AAV2/9 and AAV2/rh10 serotypes in mouse, rat and NHP in vivo after intra-nerve injections.…”
Section: Discussionmentioning
confidence: 98%
“…In 2015, Tanguy et al [60] observed a cell transduction in the sciatic nerve of mice intravenously injected with AAV2/9 one day after birth but no detail on the cell type was provided. Hoyng et al described in 2015 the transduction efficiency of AAV2/1 to 9 in rat and human Schwann cells in vitro and in sectioned mouse nerve segments undergoing demyelination ex vivo [26]. As the existing data was inconclusive, we tested AAV2/9 and AAV2/rh10 serotypes in mouse, rat and NHP in vivo after intra-nerve injections.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, around 70% of the gene therapy clinical trials for various conditions carried out so far have used modified viruses to deliver genes [55]. Lentiviral vectors can be regarded as the current gold standard in experimental gene therapy for peripheral nerve repair [57]. This may be attributed to several factors.…”
Section: Gene Delivery Systemsmentioning
confidence: 99%
“…Thirdly, choosing the right viral vector for the target cell type is essential to ensure transduction efficiency. AAV serotypes differ dramatically in their ability to target various tissues and cell types and careful selection of the serotype is required for successful transduction [57]. On the other hand, the host cell range of lentiviral vectors can be expanded or altered by modifying the viral envelope [60].…”
Section: Gene Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comparative study of nine AAV serotypes and lentiviral vectors shows that optimal transduction of rat and human Schwann cells is achieved by different serotypes. Rat nerve segments could be genetically modified equally well by a set of four AAV vectors (AAV1, 5, 7, 9), whereas AAV2 was superior in human nerve segments (Hoyng et al, 2015 ; Figure 2 ). Transduction with lentiviral vectors was, however, superior to the best AAV vectors.…”
Section: Key Areas Of Future Researchmentioning
confidence: 99%